1999
DOI: 10.1097/00000658-199908000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Bile Duct Cancer: High Resectability Rate and 5-Year Survival

Abstract: ObjectiveTo review and update the authors' experience with resectional surgery for proximal bile duct carcinoma (Klatskin tumor) and assess the role of liver resection over the past 25 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
78
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(90 citation statements)
references
References 20 publications
5
78
0
6
Order By: Relevance
“…Currently, the only way to improve outcome is to increase the resectability rate of proximal bile duct cancer. 11 In conclusion, an experienced hepatobiliary surgeon should evaluate each patient with suspicion of biliary tract carcinoma before palliative biliary drainage is initiated. 13 Helical CT and MRCP are the best imaging techniques to delineate the extent of the tumor and rule out liver metastases and enlarged lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the only way to improve outcome is to increase the resectability rate of proximal bile duct cancer. 11 In conclusion, an experienced hepatobiliary surgeon should evaluate each patient with suspicion of biliary tract carcinoma before palliative biliary drainage is initiated. 13 Helical CT and MRCP are the best imaging techniques to delineate the extent of the tumor and rule out liver metastases and enlarged lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of resectability was based on the posterior approach of the hilus, described by Launois et al 11,15 An anterior incision was made in the anterior face of Glisson's capsule, and a large curved clamp was used to place a tape around the confluence of the portal triad. This maneuver allowed the surgeon to avoid dissecting the bile duct within the hilium, thus achieving an en bloc resection of the tumor with the cellulolymphatic tissue, lymph nodes, and glissonian sheath.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Surgery provides the only chance for cure with varying resectability rates of 25-91% depending on tumour location. [3][4][5][6] However, obtaining a negative resection margin (RM) is a challenge, 7,8 and microscopic (R1) and macroscopic (R2) residual diseases are observed in 20-40% and 4-64%, respectively. [9][10][11][12][13][14][15] Many studies have revealed that positive RM of EHBD cancer is directly associated with high local recurrence (LR) rate.…”
Section: Introductionmentioning
confidence: 99%
“…2 The results of resection are also different according to type of the tumor; tumor, node, metastasis stage; and presence of tumor in the resection margins. 3 Surgery can result in cure for some patients, but this is relatively infrequent.…”
mentioning
confidence: 99%